Tunable broadband terahertz polarizer using graphene-metal hybrid metasurface - Meng, K.; Park, S. J.; Li, L. H.; Bacon, D. R.; Chen, L.; Chae, K.; Park, J. Y.; Burnett, A. D.; Linfield, E. H.; Davies, A. G.; Cunningham, J. E. (Optics Express, 2019)
We demonstrate an electrically tunable polarizer for terahertz (THz) frequency electromagnetic waves formed from a hybrid graphene-metal metasurface. Broadband (>3 THz) polarization-dependent modulation of THz transmission is demonstrated as a function of the graphene conductivity for various wire grid geometries, each tuned by gating using an overlaid ion gel. We show a strong enhancement of modulation (up to ∼17 times) compared to graphene wire grids in the frequency range of 0.2–2.5 THz upon introduction of the metallic elements. Theoretical calculations, considering both plasmonic coupling and Drude absorption, are in good agreement with our experimental findings.
Keywords: Broadband terahertz; Electrically tunable; Frequency ranges; Metallic elements; Plasmonic coupling; Strong enhancement; Terahertz frequencies; Theoretical calculations